An Analysis of Rachel's Trauma in Novel "Speak" - Firza Nur Chaerunisa; Erna Susilawati (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
This paper focuses on identifying the trauma that caused Rachel Bruin's character changes in Laurie Halse Anderson's novel "Speak". The purpose of the analysis is to determine the relationship between trauma and character development in one of the characters, Rachel. This paper applies descriptive qualitative research by identifying the triggers of trauma that happened to Rachel using Laurie Vickroy's theory and identifying character changes using Richard Kraut's theory. Based on the findings of this research, its found that the trauma Rachel experiences to be friends with Melinda again so that Rachel tends to have a worse character before she became hated with Melinda. In fact, she tried to deal with his trauma by being able to let her best friend Melinda be alone in the new season. The implication of this research is to clarify the relationship between trauma and character development in a novel narrative.